Acetylation of alpha-fetoprotein promotes hepatocellular carcinoma progression. (28th February 2020) - Xue, Junhui; Cao, Zhengyi; Cheng, Yuning; Wang, Jiyin; Liu, Yujuan; Yang, Ruixiang; Li, Hui; Jiang, Wei; Li, Gang; Zhao, Wenhui; Zhang, Xiaowei
Abstract: Alpha-fetoprotein (AFP) is a well-established biomarker for hepatocellular carcinoma (HCC). Here, we investigated the acetylation state of AFP in vivo . AFP acetylation was regulated by the acetyltransferase CBP and the deacetylase SIRT1. Acetylation of AFP at lysines 194, 211, and 242 increased the stability of AFP protein by decreasing its ubiquitination and proteasomal degradation. AFP acetylation promoted its oncogenic role by blocking binding to the phosphatase PTEN and the pro-apoptotic protein caspase-3, which increased signaling for proliferation, migration, and invasion and decreased apoptosis. High levels of acetylated AFP in HCC tissues were associated with HBV infection and correlated with poor prognosis and decreased patient survival. In HCC cells, hepatitis B virus X protein (HBx) and palmitic acid (PA) increased the level of acetylated AFP by disrupting SIRT1-mediated deacetylation. AFP acetylation plays an important role in HCC progression and provides a new potential prognostic marker and therapeutic target for HCC. Highlights: AFP acetylation status is regulated by CBP and SIRT1. Acetylation stabilizes AFP protein levels by inhibiting its ubiquitination. AFP acetylation inhibits apoptosis and promotes HCC oncogenesis. HBx and PA promote AFP acetylation. High expression of acetylated AFP in HCC tissues correlates with poor prognosis.